A critical examination of immigrant integration policies and adult education practices in South Korea - Heh Youn Shin (Adult Education Research Conference, 2020)
The purpose of this session is to facilitate a dialogue on how South Korea’s immigrant integration policies and related adult education practices at public social service agencies affect marriage immigrants’ learning and becoming in their post-migration context.
Keywords: immigration integration policy; social integration; multiculturalism; marriage immigrants